Integrated Community-based Child Survival Reproductive Health and Water and Sanitation Program in Mkuranga district, Tanzania - Mashalla Kema, Koronel; Komwihangiro, Joseph; Kimaro, Saltiel (Pan African Medical Journal)
Background: Over decades, evidence has accumulated to justify the concern that top-down approaches do not work and may result in lack of program ownership and sustainability. As a result, participatory approaches have increasingly become popular. An example of such an approach is hereby presented. Description: Working with AMREF, Mkuranga district significantly gained experience and improved its community participatory approaches in health development. AMREF’s model of Community Based Health Care (CBHC) approaches was used to implement integrated Water and Sanitation, Child Survival and Reproductive health programs. Outcomes: The project established functioning village health and water committees. A 45% increase in utilization of services was reported. Adequate nutrition status among children rose from 67.9% to 81%. Attendance of antenatal clinics rose from 35% to 70.2%. A total of 117 shallow wells, 21 boreholes and 25 rain water harvesting systems were established. Lessons learnt: Based on this experience, we conclude that in order to achieve the Millennium Development Goals (MDGs) and the National Poverty Reduction Strategy (Mkukuta) targets, building partnerships with communities who are the target beneficiaries is a prerequisite and CBHC approach is a fundamental towards attaining those goals. Conclusion: The model demonstrates that community participation is key to community empowerment, as well as community ownership and sustainability of health interventions.
A replicable model of good practices in community based health care
This article is published as part of the supplement “AMREF´s evidence in advancing the health of women and children” Supplement sponsored by AMREF - African Medical and Research Foundation © Koronel Mashalla Kema et al. The Pan African Medical Journal - ISSN 1937-8688. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Child survival